2020
DOI: 10.3389/fphys.2020.579449
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Resting and Exercise Hemodynamics Early After Heart Transplantation: A Simulation Perspective

Abstract: Introduction: During heart transplantation (HTx), cardiac denervation is inevitable, thus typically resulting in chronic resting tachycardia and chronotropic incompetence with possible consequences in patient quality of life and clinical outcomes. To this date, knowledge of hemodynamic changes early after HTx is still incomplete. This study aims at providing a model-based description of the complex hemodynamic changes at rest and during exercise in HTx recipients (HTxRs). Materials and Methods: A numerical mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 60 publications
(342 reference statements)
0
3
0
Order By: Relevance
“…Although the baroreflex and its contributions to cardiovascular physiology have been studied extensively using computational models, 3,16–20 these models do not account explicitly for the ICN. An earlier study by several of the present authors has focused on modeling the cardiac local reflex using computational neuroscience‐based approaches for detailed representations of the ion channel physiology and the biochemistry of signaling pathways 21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the baroreflex and its contributions to cardiovascular physiology have been studied extensively using computational models, 3,16–20 these models do not account explicitly for the ICN. An earlier study by several of the present authors has focused on modeling the cardiac local reflex using computational neuroscience‐based approaches for detailed representations of the ion channel physiology and the biochemistry of signaling pathways 21 .…”
Section: Introductionmentioning
confidence: 99%
“…9,13 Recent efforts by the Cardiac Consortium of the National Institutes of Health (NIH) Common Fund Stimulating Peripheral Activity to Relieve Conditions (SPARC) program have delineated extensively the anatomical, connectional, molecular, and physiological aspects of the ICN. 6,14,15 Although the baroreflex and its contributions to cardiovascular physiology have been studied extensively using computational models, 3,[16][17][18][19][20] these models do not account explicitly for the ICN. An earlier study by several of the present authors has focused on modeling the cardiac local reflex using computational neuroscience-based approaches for detailed representations of the ion channel physiology and the biochemistry of signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…For a period of ~2 years post-HT, the current subject reported that he was unable to elevate exercise HR above 150 bpm, but during the present test, a slightly higher HR of 159 bpm was recorded. Chronotropic response from denervation during HT surgery and V˙O 2peak have been demonstrated to improve over time and through structured exercise (18,30). Sympathetic reinnervation post-HT is less likely with age; however, other adaptions to muscle tissue can alter factors that influence V˙O 2peak (4,29).…”
Section: Discussionmentioning
confidence: 99%